2019
DOI: 10.1136/bmjopen-2018-026027
|View full text |Cite
|
Sign up to set email alerts
|

Intended place of residence in old age of internal migrants aged 15–64 years: a citywide cross-sectional study in Shanghai, China

Abstract: ObjectivesTo explore the intentions of working-age internal migrants concerning their place of residence in old age and the relevant influencing factors.MethodA cross-sectional survey was conducted in the 17 districts of Shanghai, China in 2013. Through multi-stage stratified sampling with probability proportional to size, 7968 internal migrants (aged 15–64 years) were selected and interviewed individually face to face. The primary outcome concerned the intended place of residence in old age of internal migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Wen Chen [10] found that the NCMS effectively reduced the proportion of out-of-pocket medical expenses in the total family expenditure for rural and urban migrants aged 15-59, but did not study the impact of the NCMS on elderly migrants. Jing Zhao et al [21] found that participation in Shanghai's health insurance increased the likelihood of the intentions for migrants aged 15-64 staying in Shanghai rather than returning to their hometown in their old age. Bo-li Peng et al [22] found that rural-to-urban migrants aged 15-59 with the NCMS were more likely to return to their former residence for medical treatment, and less likely to live permanently in the relocation area.…”
Section: Introductionmentioning
confidence: 99%
“…Wen Chen [10] found that the NCMS effectively reduced the proportion of out-of-pocket medical expenses in the total family expenditure for rural and urban migrants aged 15-59, but did not study the impact of the NCMS on elderly migrants. Jing Zhao et al [21] found that participation in Shanghai's health insurance increased the likelihood of the intentions for migrants aged 15-64 staying in Shanghai rather than returning to their hometown in their old age. Bo-li Peng et al [22] found that rural-to-urban migrants aged 15-59 with the NCMS were more likely to return to their former residence for medical treatment, and less likely to live permanently in the relocation area.…”
Section: Introductionmentioning
confidence: 99%